A survey of patients with palliative needs on an acute medical admissions unit. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Quibell, Rachel; Armstrong, Leonie; Jaafar, Ahmed; Muir, Michelle; Price, Ashley; Woolley, Sara
Abstract : Aims: To identify any current issues for patients with palliative needs being admitted to an acute medical admissions unit To inform and prioritise the work of the Specialist Palliative Care Team (SPCT) for emergency medical admissions. To map the pathway for patients with palliative and end of life care needs. This work was prompted by a Marie Curie Delivering Choice Programme report1. Methods: Two week Pilot Survey followed by a 6 month CNS led Project with data collection. Pilot Survey Patients, with palliative care needs, irrespective of diagnosis were identified by consulting nursing and medical staff and all medical notes each day. Data collected via notes analysis- Demographics GP Reason for admission and any known patient history DNAR Status Discharge Packages of Nursing and Social Care at home Medication Specialist palliative care involvement Results: From Pilot Survey Themes: Palliative Care Needs in unit. 24 patients identified in 2 weeks 25% were actually referred to SPCT. 3/24 patients commenced on Liverpool Care Pathway for the Dying and died on unit. Out of Hours Need: 62.5% admitted OOH Referral Source: 29% care homes, 50% A&E Documentation and Information: 71% had DNAR documentation in notes 4% were documented as on GP Palliative Care Register 6 month Project data will be available for poster, and this will contain additional information on palliative care needs and symptoms. Conclusion: There are significant palliative care needs on an acute medical admissions unit. This survey will inform the direction and design of palliative care provision on a busy acute medical admissions unit. It also gives invaluable information regarding the patient pathway prior to admission and after discharge from medical admissions to a base ward.